Gedung Koser Musik Di Pekanbaru Dengan Menggunakan Prinsip Perancangan Peter Eisenman - M Gema Indrawan; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
A public enthusiasm on music is not well-framed by availability of facilities in order to accommodate musical community in Pekanbaru. Therefore, a musical concert hall is needed. Concert hall is a building which can be used as a place to hold a music concert lively. To express music on building,design of the hall has used a deconstruction architectural approach, that is based in design principles oby Peter Eisenman. The principles are using simple geometry, grid pattern, and displacement, that are combined within harmony concept. Those have applied on site, building mass, and facade. On site, grid pattern is formed by dividing site into sections and making the pattern following main access. Geometrical shape is transformed by displacing and by following the grid pattern on site. Whereas the building facade uses rectangle which rotated as a result from the displacement.Keywords: Concert Hall, Eisenman, Geometry, Grid, Displacement